Population pharmacokinetics and standard uptake value ratio of aducanumab, an amyloid plaque-removing agent, in patients with Alzheimer's disease - Kumar Kandadi Muralidharan; Xiao Tong; Kenneth G. Kowalski; Raj Rajagovindan; Lin Lin; Samantha Budd Haberlain; Ivan Nestorov (Wiley, 2022)
Abstract Aducanumab is a human immunoglobulin G1 anti‐amyloid beta (Aβ) antibody currently being evaluated for potential treatment of patients with early Alzheimer's disease. This paper describes the relationship between the population pharmacokinetics (PopPKs) and pharmacokinetics‐pharmacodynamics (PKs‐PDs) of aducanumab using data from phase I to III clinical studies, with standard uptake value ratio (SUVR) used as a PD marker. Across clinical studies, aducanumab was administered intravenously either as a single dose ranging from 0.3 to 60 mg/kg or as multiple doses of 1, 3, 6, or 10 mg/kg every 4 weeks. A titration regimen with maintenance doses of 3, 6, or 10 mg/kg was also evaluated. Aducanumab PK was characterized with a two‐compartment model with first‐order elimination. No nonlinearities in PKs were observed. The PopPK‐PD model was developed using a sequential estimation approach. The time course of amyloid plaques, as expressed by composite SUVR measured using positron emission tomography, was described using an indirect response model with drug effect stimulating the elimination of SUVR. None of the identified covariates on PK and the PopPK‐PD model were clinically relevant. The PopPK‐PD model showed that magnitude, duration, and consistency of dosing are important factors determining the degree of Aβ removal. The intrinsic pharmacology of aducanumab remained consistent across studies.